2021
DOI: 10.1080/02813432.2021.1935048
|View full text |Cite
|
Sign up to set email alerts
|

Personal responsibility for health? A phenomenographic analysis of general practitioners’ conceptions

Abstract: Objective: To analyse and describe general practitioners' perceptions of the notion of a 'personal responsibility for health'. Design: Interview study, phenomenographic analysis. Setting: Swedish primary health care. Subjects: General Practitioners (GPs). Main outcome measures: Using the phenomenographic method, the different views of the phenomenon (here: personal responsibility for health) were presented in an outcome space to illustrate the range of perceptions. Results: The participants found the notion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Studies indicated that individuals are accountable for lifestyle choices and risks that could have been avoided [ 33 , 34 , 37 39 , 41 – 43 , 47 , 48 , 56 ], attempting to make the best choices for their health [ 33 , 35 , 52 , 56 ] and implementing health promotion and healthy living and safe activities [ 49 , 51 ]. A study highlighted patient responsibilities, which included being truthful, providing a complete medical history, requesting information or clarification, complying with physician instructions, meeting financial obligations, being cognizant of the costs associated with healthcare, using medical resources judiciously and discussing the end of life decisions and organ donation [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies indicated that individuals are accountable for lifestyle choices and risks that could have been avoided [ 33 , 34 , 37 39 , 41 – 43 , 47 , 48 , 56 ], attempting to make the best choices for their health [ 33 , 35 , 52 , 56 ] and implementing health promotion and healthy living and safe activities [ 49 , 51 ]. A study highlighted patient responsibilities, which included being truthful, providing a complete medical history, requesting information or clarification, complying with physician instructions, meeting financial obligations, being cognizant of the costs associated with healthcare, using medical resources judiciously and discussing the end of life decisions and organ donation [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…This highlights the importance of individualized care or patient-oriented care [ 49 ]. Thus, patients should be willing to accept help for their care while also keeping in mind that their health is under their control instead of completely shifting their roles onto their healthcare providers [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive ideas like free choice and personal responsibility unfortunately may harm health and well-being [27]. Certainly, such statements can be positive and empowering 28].…”
Section: Concern Regarding Personal Freedoms and Autonomymentioning
confidence: 99%
“…However, trying to uncover how health care professionals deal with ethical issues is methodologically complex, partly because the term ‘ethical issues’ lacks a clear definition [ 8 10 ]. Literature in ethics further displays broad and varied concepts aiming to capture dealing with ethical issues ranging from considerations [ 11 ], perspectives [ 12 , 13 ], views [ 14 , 15 ], conceptions [ 16 ], moral values [ 17 ], ethical reasoning [ 18 , 19 ], justifications [ 20 ], and decision-making [ 21 , 22 ]. Even if there are considerable differences between these concepts, they also point to the intricate methodological problems of trying to capture the dealing with ethical issues in the clinical context of patients and clinicians.…”
Section: Introductionmentioning
confidence: 99%